Alterations in synapses and mitochondria induced by acute or chronic intermittent hypoxia in the pre-Bötzinger complex of rats: an ultrastructural triple-labeling study with immunocytochemistry and histochemistry - Kang, Junjun; Lu, Naining; Yang, Shoujing; Guo, Baolin; Zhu, Yuanyuan; Wu, Shengxi; Huang, Xiaofeng; Wong-Riley, Margaret T. T.; Liu, Ying-Ying (Frontiers in Cellular Neuroscience, 2023)
The pre-Bötzinger complex (pre-BötC), a kernel of inspiratory rhythmogenesis, is a heterogeneous network with excitatory glutamatergic and inhibitory GABAergic and glycinergic neurons. Inspiratory rhythm generation relies on synchronous activation of glutamatergic neuron, whilst inhibitory neurons play a critical role in shaping the breathing pattern, endowing the rhythm with flexibility in adapting to environmental, metabolic, and behavioral needs. Here we report ultrastructural alterations in excitatory, asymmetric synapses (AS) and inhibitory, symmetric synapses (SS), especially perforated synapses with discontinuous postsynaptic densities (PSDs) in the pre-BötC in rats exposed to daily acute intermittent hypoxia (dAIH) or chronic intermittent hypoxia (CIH). We utilized for the first time a combination of somatostatin (SST) and neurokinin 1 receptor (NK1R) double immunocytochemistry with cytochrome oxidase histochemistry, to reveal synaptic characteristics and mitochondrial dynamic in the pre-BötC. We found perforated synapses with synaptic vesicles accumulated in distinct pools in apposition to each discrete PSD segments. dAIH induced significant increases in the PSD size of macular AS, and the proportion of perforated synapses. AS were predominant in the dAIH group, whereas SS were in a high proportion in the CIH group. dAIH significantly increased SST and NK1R expressions, whereas CIH led to a decrease. Desmosome-like contacts (DLC) were characterized for the first time in the pre-BötC. They were distributed mainly adjacent to synapses, especially SS. Mitochondria were found in proximity to the DLC. Findings of single spines with dual AS and SS innervation provide morphological evidence of excitation-inhibition interplay within a single spine in the pre-BötC. In particular, we characterized spine-shaft microdomains of concentrated synapses coupled with mitochondrial positioning that could serve as a structural basis for synchrony of spine-shaft communication. Mitochondria were found within spines and ultrastructural features of mitochondrial fusion and fission were depicted for the first time in the pre-BötC. Thus, we provide ultrastructural evidence that excitation-inhibition synapses in shafts and spines coincide with mitochondrial dynamic in their contribution to respiratory plasticity in the pre-BötC.